Calcificaciones cerebrales extensas y corea, en hipoparatiroidismo probablemente posquirúrgico - Lira, David (2009)
Introduction: Cerebral calcifications may be unilateral or bilateral; unilateral etiology may include infections, trauma or stroke and bilateral may be physiologic, metabolic or idiopathic. Case report: Female 48 year-old patient who had thyroidectomy 27 years before, received levothyroxine, and who was attended for chorea, ballistic involuntary movements and progressive difficulty in walking. She presented right sided hypotonia, right upper limb winding movements, hypocalcemia, hyperphosphatemia and low parathormone levels; tomography and magnetic resonance showed bilateral calcifications in brain basal ganglia and cerebellum. She was treated with calcium citrate, calcitriol and risperidone with complete recovery. Discussion: Patients with basal ganglia calcifications have extrapyramidal symptoms (20-30%) such as parkinsonism or coreoatetosis, seizures, and neuropsychiatric disorders. Brain bilateral calcifications usually consist in calcium and other minerals deposit. Hypoparathyroidism is frequent complication of radical thyroidectomy accompanied with hypocalcemia, hyperphosphatemia and parathormone low concentration as the case described. Some patients do not develop symptoms immediately. Treatment improves symptoms but not calcifications; in our patient improvement would be due to calcium normalization more than risperidone treatment.